Biological activities of the aerial and undergound parts of Gymnadenia nigra Rchb.f. (syn. Nigritella nigra (L.) Rchb. f.) from the Italian Alps - Vitalini, Sara; Rubin, Beatrice; Monticelli, Halenya; Barollo, Susi; Redaelli, Marco; Bertazza, Loris; Mian, Caterina; Zorzan, Maira; Garzoli, Stefania; Iriti, Marcello; Pezzani, Raffaele (Natural Product Research, 2023)
: This study investigated the bioactivity of both aerial (GNAR) and underground (GNUG) parts of Gymnadenia nigra Rchb.f. (syn. Nigritella nigra (L.) Rchb. f.) (Orchidaceae). The obtained data proved interesting when the samples were tested in two adrenocortical cancer cell lines (SW13 and H295R). In particular, the GNAR 80% methanol extract distinctly inhibited their viability after 24 h at a concentration of 1 μg/μL by MTT assay and trypan blue dye exclusion method. Cell morphology evaluation by means Wright's staining also showed significant results, particularly in SW13 cells under the effect of both extracts. GNAR extract was able to scavenge the DPPH radical better than GNUG extract. It also was more active in albumin denaturation (a maximum % denaturation equal to 463.0 ± 8.3 vs 77.3 ± 13.3) and protease inhibition (a maximum % inhibition equal to 138.5 ± 7.0 vs 2.1 ± 2.0) tests. The results highlighted an important antitumor activity of G. nigra in vitro that deserves to be further studied.